The triglyceride-glucose index and risk of cognitive impairment: a systematic review and meta-analysis with inclusion of two national databases - Yang, Ying; Peng, Pai; Huang, Huadong; Zhao, Yanan; Li, Yating; Xu, Xiao; Jiang, Shixie; Yang, Yanrong; Pan, Gaofeng; Wen, Yanting; Wu, Dan; Chen, Shanping; et al. (Frontiers in Neurology, 2024)
BackgroundTo investigate the relationship between the triglyceride and glucose (TyG) index and cognitive impairment (CI).MethodsFive authoritative databases were systematically searched for potentially relevant studies on ‘TyG index’ and ‘CI’ from inception to 27 April 2024. Two representative databases from the United Kingdom and United States were also included. We used the PICOS criteria to select available articles. All data was combined to compute Odd Ratios (ORs).Results15 studies were included in the meta-analysis (participants: 5604303). The pooled effect sizes demonstrate that individuals with a high TyG index exhibit a significantly elevated risk of CI compared to those with a low TyG index (OR = 2.16, 95%CI: 1.51; 3.08, p < 0.001). The subgroup analysis showed that inpatients with a high TyG index exhibited an increased risk of CI (OR = 4.56, 95%CI: 3.09; 6.74, p < 0.001). Furthermore, the risk of developing distinct types of CI differed significantly [CI: OR = 1.64, 95% CI: 1.29; 2.07, p < 0.001; Vascular Cognitive Impairment (VCI): OR = 5.39, 95% CI: 3.33; 8.70, p < 0.001].ConclusionA positive correlation exists between the TyG index and risk of CI, which has potential value in optimizing CI risk stratification among elderly people, especially those hospitalized.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023450336.